Il dolore tra medicina razionale e medicine "parallele" - Pain between rational and "parallel" medicines - Germana Pareti (Publiediting, 2012)
This short review aims to illustrate some topics of an international symposium recently held in Paris, dedicated to the comparison of rational and "parallel" medicines in the ancient world, but also with references to the modern and contemporary history. In this context the treatment of pain deserves attention, since in the history of medicine it has always been associated with the disease, and considerable efforts have made to suppress it. Two contributions have dealt with the placebo/nocebo effects, recostructing their history, highlighting both neurobiological and psychological mechanisms triggering them, and showing the bioethical implications deriving from induction of nocebo. Although the neural processes underlying these effects were not known to the science of the past, certain pratices were, however, used not only by doctors, but also by the Church to influence the ignorant people.